Thymoma associated myasthenia gravis (TAMG): differential expression of functional pathways in relation to MG status in different thymoma histotypes - Yamada, Yosuke; Weis, Cleo-Aron Thias; Thelen, Julian; Sticht, Carsten; Schalke, Berthold; Ströbel, Philipp; Marx, Alexander (Frontiers in immunology, 2020)
A unique feature of thymomas is their unrivaled frequency of associated myasthenia gravis (MG). Previous studies reported that MG+ thymomas contain a larger number of mature ‘pre-emigrant’ CD4+ T cells than MG- thymomas and that most thymomas do not contain AIRE expressing cells irrespective of MG status. These findings suggest that CD4+ T cells that mature inside the abnormal microenvironment of thymomas and egress to the blood are critical to the development of thymoma-associated MG (TAMG) irrespective of thymoma histotype. However, underlying mechanisms have remained enigmatic. Since gene expression profiles are different among thymoma histological subtypes, we hypothesized that the mechanisms leading to TAMG might also be different. To test this hypothesis, we compared the expression of functional pathways with potential immunological relevance (N=380) in relation to MG status separately in type AB and B2 thymomas, using the TCGA data set. We found that <10% of the investigated pathways were differentially upregulated or downregulated in MG+ compared to MG- thymomas with significant differences between AB and B2 thymomas. Unexpectedly, some MG-associated pathways that were significantly upregulated in AB thymomas were significantly downregulated in B2 thymomas, as exemplified by oxidative phosphorylation pathway. Conversely, the MG-associated pathway related to ‘macrophage polarization’ was downregulated in MG+ AB thymoma and upregulated in MG+ B2 thymoma. Our results suggest that the mechanisms leading to TAMG might be different among thymoma histological subtypes. Functions related to metabolisms, vascular and macrophage biology appear as promising new candidate mechanisms involved in the pathogenesis of TAMG.